A circular approach to the e-waste valorization through urban mining in Rio de Janeiro, Brazil. (10th July 2020) - Ottoni, Marianna; Dias, Pablo; Xavier, Lúcia Helena
Abstract: Electronic waste (e-waste or WEEE) is one of the most critical categories regarding the decision-making for waste management. Brazil is the second major e-waste producer in Americas, after USA, with 1.5 million tones generated annually. However, the absence of adequate system for e-waste reverse logistics are a reality in most of the Brazilian cities. Concerning this hypothesis, we proposed a scenario analysis to support decision-making in e-waste management. This study analyzed the e-waste amount generation, the location of the recycling companies of this segment and the collection routes in the metropolitan region of Rio de Janeiro (MRRJ). Besides, we proposed a set of criteria and indicators to identify the best option for e-waste management. The analysis indicates that Rio de Janeiro is the biggest e-waste producer of the MRRJ, with an amount of approximately 127 ton/day, corresponding to 251 collection points, which represents a high discrepancy in relation to the other municipalities of MRRJ. The findings point out that indicators, such as the Gross Domestic Product (GDP) and Municipal Human Development Index (MHDI), could be used as an alternative for a more accurate analysis for a sustainable urban grid design. This study identified 24 e-waste recycling industries that services the current demand of the MRRJ, most of them concentrated in the central and south portions of the MRRJ, which coincide with the municipalities with the biggest e-waste generation rates. Some hotspots, however, are isolated from the recycling industries, as observed at the MRRJ extremes. In order to provide a better choice for e-waste reverse logistics routes, we proposed 12 indicators, in environmental, economic and social dimensions. Thirty-five hotspots were identified and divided in five main routes according to the recycling industries nearby and the local roads. Urban mining of e-waste seems to be an interesting alternative for secondary raw material recovery, especially in an emerging economy country like Brazil, that consumes huge amounts of electronic devices and demands solutions compatible with environmental law requirements. Hence, this study contributes for a more sustainable development pattern regarding e-waste management in the country, since it reinforces the importance of circularity.